Dampak Teknologi terhadap Nilai Moral dan Agama pada Anak Usia Dini - Widya Nurkayatin; Muhammad Turhan Yani; Achmad Sya’dullah (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2024)
The development of information technology in the modern era is increasingly rapid. and influences various aspects of life, including early childhood education. The Internet, as a component of information technology, connects computers around the world into a very large network, enabling instant and global exchange of information. This has a significant impact on Religious and Moral Competencies in AUD. The qualitative approach used in this research is a case study design at the Bung Karno State Kindergarten. Data was collected through classroom observations, semi-structured interviews with PAUD teachers, and questionnaires for parents or guardians of students. The research results show that technology, especially the use of gadgets, has a significant influence on the moral and religious values ​​of young children. Children who use technology excessively tend to have difficulty socializing, have apathetic behavior, and show signs of addiction. Challenges in teaching moral and religious values ​​​​include the difficulty of conveying abstract concepts to children who are still at the fundamental cognitive development stage. This research concludes that moral and religious education needs to be fostered from an early age to form quality character. Although technology can facilitate various activities, uncontrolled use can have a negative impact on children's moral and religious development. Therefore, parents, educators and other stakeholders need to do better to manage the use of technology and strengthen the education of moral and religious values ​​​​in early childhood.